Nursing Supervision Model Development for Cancer Patients Receiving Chemotherapy at Udonthani Cancer Hospital - Phanjungharn, Banyat; Juntachum, Wanchanok (Medical Journal of Sakon Nakhon Hospital, 2024)
This action research was to develop the nursing supervision model for cancer patients receiving chemotherapy at Udon thani cancer hospital and compare nurses’ competency scores before and after using this model. The target groups were 8 professional supervisory nurses and 30 nurses being supervised with the model. The study process was divided into 4 steps: 1) planning phase, analyzed the situational problem and developed the supervision model jointly between supervisors and supervisees 2) the operational phase, it was to implement a supervision model 3) the observation phase, it was to observe and evaluate supervisees’ performance and 4) the reflection phase, providing the feedback and compare nurses’ competency scores before and after model implementation. The research tool was a 5–point scale of nursing competency questionnaire on cancer patients receiving chemotherapy. The content validity was explored by 5 experts and Cronbach’s alpha reliability coefficient was 0.88. Data were analyzed by frequency, percentage, average, standard deviation and paired sample t–test. A p value less than 0.05 was considered statistically significant. The study revealed that: 1. The developed supervision model consisted of 1) standards of care for cancer patients receiving chemotherapy to safety 2) contract and participation for supervision plan 3) supervision action for development of professional knowledge and skills 4) reflection for feedback and 5) supportive function. 2. After supervision model implementation, the nurse supervisees’ competency scores was statistically significant increased compared to those before model implementation ( = 4.25, S.D. = 0.30, = 3.22, S.D. = 0.25, respectively, t = 13.05, df = 29, p = 0.000).